Peranan Pemerintah melalui Intervensi Pasar dalam Perspektif Islam - Santi Merlinda; Riqa Aniqa Helma Alam; Qorry Anggita Rishaq (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
The increased world crude oil prices (BBM) caused the soaring price of fuel oil in Indonesia in 2011. The rise in fuel prices multiplies in all sectors of the economy, from transportation and production costs to inflation. This study aims to know Government Intervention in the market from an Islamic Perspective in the case of rising fuel prices in Indonesia, through a qualitative approach, with case studies and documentary methods. In this case, the Indonesian government intervened by setting prices for several fuel commodities such as diesel, premium and pertalite. The government's role in fuel price intervention is permitted from an Islamic perspective, as long as it aims to increase the benefit of the community and protect the people's interests, such as reducing costs.